The Relationship between Sleep Quality and Physical Fatigue in the Elderly - Salsa Sasmita Ismail; Mulyadi, Mulyadi; Watung, Grace I.V (Bantayang Omni Cendekia, 2025)
Background: Elderly (elderly) is the final period in human life where a person begins to experience changes in his life which are characterized by physical, psychological and cognitive changes. Objective: This study aims to determine the relationship between sleep quality and physical fatigue in the elderly. Methods: This study uses quantitative research using an analytical descriptive method with a cross sectional approach. The sampling technique in this study is Stratifeid Random Sampling with a total of 75 samples. Data collection using questionnaires. Results: The results of the statistical test using the Chi-square test obtained a p-value = 0.002 that is smaller than the p-value ≤0.05 which means that Ho is rejected, then there is a relationship between sleep quality and physical fatigue in the elderly. Conclusion: There is a significant and strong relationship between sleep quality and physical fatigue in the elderly. It is expected that health workers will increase public knowledge about sleep quality with physical fatigue in the elderly through socialization and seminars so that the public can understand the importance of good sleep quality.